Organizational Synergy, Dissonance and Spinoffs - Mili Shrivastava; T.V.S. Ramamohan Rao (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Spinoff firms are exceptional performers across industries. The causes for the emergence of spinoff firms are widely investigated in the literature. However, the role of teams for spinoffs has received little scholarly attention. On one hand, talented individuals may find it necessary to team up with others to utilize complementary knowledge and generate synergies. On the other hand, some types of team production environments may have dissonance and motivate individuals to leave the team. The present study demonstrates that organizational synergies and dissonance can be incorporated into appropriate specifications of team production functions. This framework explains the necessity to form a team, stability of teams, and the emergence of different types of spinoffs depending on specific organizational arrangements.
Keywords: D23; D85; D02; 330; organizational synergy; production functions; spinoffs; Betriebsaufspaltung; Arbeitsgruppe; Produktionsfunktion; Synergie; Arbeitspsychologie; Theorie